PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS V DI SEKOLAH DASAR - Septian, Wella Mada; Syahrial; Issaura Sherly Pamela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
A This research is motivated by the low learning activity of class V students at SDN 120/1 Simpang Jelutih. Student learning activity in learning is less visible, learning communication occurs in one direction, and learning stages only refer to what is in the learning book. This research is a Classroom Action Research that aims to describe the increase in student learning activity through cooperative learning of the index card match type in mathematics learning in class V of SDN 120/1 Simpang Jelutih. This research was conducted at SDN 120/1 Simpang Jelutih in September-October 2024. Research data were obtained by observation and documentation. Research data were analyzed qualitatively and quantitatively. This research was carried out in two cycles and each cycle consisted of two meetings with the following stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of the study show that implementing cooperative learning of the index card match type in the learning process can increase student learning activity. This increase can be seen in the data analysis of each meeting cycle. Cycle I meeting I achieved a success of 53.12%, cycle I meeting II achieved a success of 62.5%, cycle II meeting I achieved a success of 68.75%, in cycle II meeting II achieved a success of 78.12% which increased by 9.38%. Based on the results of the study, it can be concluded that the application of the index card match type cooperative learning model can increase student learning activity in mathematics learning in grade V of Elementary School. Proven by the success of this study. Student learning activity can be increased by using the index card match type cooperative learning model.